Use of Olive Oil Industrial By-Product for Pasta Enrichment - Lucia Padalino; Isabella D'Antuono; Miriana Durante; Amalia Conte; Angela Cardinali; Vito Linsalata; Giovanni Mita; Antonio F. Logrieco; Matteo Alessandro Del Nobile (MDPI AG, 2018)
Background: During recent years food industries generally produce a large volume of wastes both solid and liquid, representing a disposal and potential environmental pollution problem. Objective: The goal of the study was to optimize, from both sensory and nutritional points of view, the formulation of durum wheat spaghetti enriched with an olive oil industrial by-product, indicated as olive paste. Methods: Three consecutive steps were carried out. In the first one, the olive paste was air-dried at low temperature, milled to record olive paste flour and properly analyzed for its biochemical composition. In the second step, the olive paste flour was added to the pasta dough at 10% and 15% (w/w). In the last step, different concentrations of transglutaminase were added to enriched pasta (10% olive paste) to further improve the quality. Sensory properties and nutritional content of enriched and control pasta were properly measured. Results: Spaghetti with 10% olive paste flour and 0.6% transglutaminase were considered acceptable to the sensory panel test. Nutritional analyses showed that addition of 10% olive paste flour to pasta considerably increased content of flavonoids and total polyphenols. Conclusions: The proper addition of olive paste flour and transglutaminase for pasta enrichment could represent a starting point to valorize olive oil industrial by-products and produce new healthy food products.